Juan Ramón Jiménez and Nietzsche - John P. Devlin (Studies in 20th & 21st Century Literature, 1983)
The young Juan Ramón Jiménez shared the enthusiasm for the writings of Nietzsche prevalent among his contemporaries. More significant are the interest in and affinity with Nietzsche which persisted into the poet's maturity. Jiménez found in Nietzsche not only a man of ideas but a poet who claimed to be a potent spiritual force. Both writers held that the modern age could recover a sense of spiritual integrity through the will of the individual to live and interpret human existence as an aesthetic phenomenon. Nietzsche's views on the nature of art and the role of the artist helped to sustain Jiménez' exalted and elitist view of poetry and the poet's mission. Jiménez felt an ethical kinship with the philosopher who asserted the absolute uniqueness of the creative individual, the end of whose existence was self-realization through his art. Nietzsche's doctrine of heroic vitalism as an antidote to chronic spiritual malaise corresponds to Jiménez' revitalized vision of the poetic word proclaimed in the Diario and elaborated in subsequent verse and prose writings.
Keywords: Juan Ramón Jiménez; Nietzsche; German poetry; Spanish poetry; aesthetic; nature of art; artist; philosophy; self-realization; spiritual; Diario